Human Capital Architecture and Its Role in Sustaining Strategic Innovation - Taat Kuspriyono (Pusat Riset dan Inovasi Nasional, 2026)
This paper examines the role of human capital architecture in sustaining strategic innovation in increasingly dynamic and uncertain environments. It addresses the problem that many organizations struggle to translate human capital investments into consistent innovation outcomes due to misalignment, resistance to change, and resource constraints. The objective is to synthesize recent literature (2020–2026) to clarify how elements such as leadership, organizational culture—particularly psychological safety—and talent systems contribute to innovation capability and performance. Using a conceptual literature review approach based on Scopus- and Web of Science-indexed sources, the study integrates empirical and theoretical insights into a coherent framework. The findings indicate that human capital architecture drives innovation through leadership and culture as key mechanisms, while constraints such as limited resources and resistance moderate these relationships, and continuous evaluation systems enhance adaptability. The paper concludes that organizations that intentionally align human capital strategies with innovation priorities, supported by ongoing measurement and feedback, are better positioned to achieve sustained competitive advantage.